Teachers' Perception Of Developing Students' Critical Thinking Through Controversial Issues Discussion - Fattah Hanurawan; Peter Waterworth (Universitas Negeri Malang, 2016)
This project sought to explore the perception about processes used by four teachers in Australia and Indonesia on their use of controversial discussions in developing critical thinking in everyday teaching. The comparative case study data were collected using guided interviews and analyzed by a thematic analysis. Analysis was validated by feedback from the subjects. The research found that there were variations in Indonesian and Australian teachers' perceptions about developing critical thinking in students through discussing controversial issues. Adequate pre-service and in-service training was necessary to provide teachers with the confidence and skill to open up discussion of difficult and divisive community issues